2016
DOI: 10.1007/s00122-016-2810-3
|View full text |Cite
|
Sign up to set email alerts
|

Breeding progress, environmental variation and correlation of winter wheat yield and quality traits in German official variety trials and on-farm during 1983–2014

Abstract: Key message Over the last 32 years, a large gain in grain yield (24 %) was achieved in official German variety trials, and despite considerable loss in protein concentration (−7.9 %), winter wheat baking quality was partially improved over the last 32 years. On-farm gain in grain yield (32 %) exceeded gain in trials, but at yield level about 25 dt ha −1 lower. Breeding progress was very successfully transferred into both progress in grain yield and on-farm baking quality. AbstractLong-term gains in grain yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
136
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(170 citation statements)
references
References 27 publications
26
136
3
5
Order By: Relevance
“…For the period 1983-2014, a large gain in grain yield of winter wheat in official variety trials (24%) and on farms (32%) was achieved in Germany [34]. Additionally, a slight increase in better yield stability of newer wheat cultivars has been found retrospectively based on the analysis of German official variety trials from 1983-2014 [34]. This effect was also mentioned by nearly half of the respondents in this study (Table 10).…”
Section: Cultivar Choice and Plant Breedingsupporting
confidence: 56%
See 1 more Smart Citation
“…For the period 1983-2014, a large gain in grain yield of winter wheat in official variety trials (24%) and on farms (32%) was achieved in Germany [34]. Additionally, a slight increase in better yield stability of newer wheat cultivars has been found retrospectively based on the analysis of German official variety trials from 1983-2014 [34]. This effect was also mentioned by nearly half of the respondents in this study (Table 10).…”
Section: Cultivar Choice and Plant Breedingsupporting
confidence: 56%
“…Based on the re-analysis of official variety trials of the United Kingdom over the period 1948-2007 for winter wheat, at least 88% of the improvement in grain yield can be attributed to genetic improvement, with only 12% ascribed to changes in agronomy [33]. For the period 1983-2014, a large gain in grain yield of winter wheat in official variety trials (24%) and on farms (32%) was achieved in Germany [34]. Additionally, a slight increase in better yield stability of newer wheat cultivars has been found retrospectively based on the analysis of German official variety trials from 1983-2014 [34].…”
Section: Cultivar Choice and Plant Breedingmentioning
confidence: 99%
“…Because of the high cost of the multienvironment trials, it is extremely important to obtain high‐quality information. Many authors demonstrate that it is possible to use these data to perform meta‐analyses and measure the genetic gains in a variety of crop species (Oury et al, 2012; Qin et al, 2015; Balota et al, 2017; Laidig et al, 2017).…”
mentioning
confidence: 99%
“…The absence of this condition will result in high FN values, even in susceptible genotypes. Laidig et al (2017) analyzing data from VCU trials in Germany also observed that FN was highly influenced by environment.…”
Section: Resultsmentioning
confidence: 96%
“…In Triticum durum L. there are genetic gain reports of bread-making quality (De Vita et al, 2007;Subira et al, 2014). In T. aestivum there are evidences of high bread-making quality parameters in modern genotypes (Hucl et al, 2015;Ormoli et al, 2015;Sanchez-Garcia et al, 2015, Laidig et al, 2017. Nonetheless, genetic gain references for bread-making quality are insufficient.…”
Section: Introductionmentioning
confidence: 99%